2010
DOI: 10.1186/1471-2407-10-426
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between cancer driver and passenger gene alteration candidates via cross-species comparison: a pilot study

Abstract: BackgroundWe are developing a cross-species comparison strategy to distinguish between cancer driver- and passenger gene alteration candidates, by utilizing the difference in genomic location of orthologous genes between the human and other mammals. As an initial test of this strategy, we conducted a pilot study with human colorectal cancer (CRC) and its mouse model C57BL/6J ApcMin/+, focusing on human 5q22.2 and 18q21.1-q21.2.MethodsWe first performed bioinformatics analysis on the evolution of 5q22.2 and 18q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Another study [34] also demonstrated that HSV-1 infection in human brain cell can induce the expression of miR-146a. Apparently, these findings not only indicate that miR-146a takes a functional role in immune response as a regulatory factor, but also suggest that its dynamic activity (expression), in some specific contexts, may just serve as the passenger of disease and/or immune processes [10]. This is exactly the main message conveyed by the module p-modu-4-ps where the positive correlations between the modular miRNAs and genes could not be simply explained by a regulator-target mechanism.…”
Section: Resultsmentioning
confidence: 92%
“…Another study [34] also demonstrated that HSV-1 infection in human brain cell can induce the expression of miR-146a. Apparently, these findings not only indicate that miR-146a takes a functional role in immune response as a regulatory factor, but also suggest that its dynamic activity (expression), in some specific contexts, may just serve as the passenger of disease and/or immune processes [10]. This is exactly the main message conveyed by the module p-modu-4-ps where the positive correlations between the modular miRNAs and genes could not be simply explained by a regulator-target mechanism.…”
Section: Resultsmentioning
confidence: 92%
“…We performed bi-directional exon-resequencing as previously described [23] to investigate sequence mutations in APC exons in these sporadic canine colorectal tumors. Specifically, we sequenced 14 of the 15 coding exons (as we could not design efficient primers to amplify exon 4) with 8,454 bases total for the canine APC gene, and were able to assemble the entire exon sequences from the forward and reverse sequences of the mostly overlapping PCR products in many cases, as described previously [23].…”
Section: Resultsmentioning
confidence: 99%
“…Primer design and PCR amplification of exons of the chosen genes, as well as bi-directional sequencing of the PCR products were performed at The J. Craig Venter Institute in Maryland as previously described [23]. Base-calling using the software Phred (www.phrap.org/phredphrapconsed.html), sequence trimming with the software Lucy (www.tigr.org/software/sequencing.shtml), exon sequence assembly, as well as comparison with the published dog reference genome [1] for mutation detection were performed as described [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of miR-146a in the immune response has been widely investigated. Past studies suggest that miR-146a plays a functional role in immune response as a regulatory factor and its expression may serves as the passenger of disease and/or immune processes (Cameron et al , 2008; Lukiw et al , 2008; Hill et al , 2009; Curtale et al , 2010; Ji et al , 2010). This is exactly the main message conveyed by the module modu-1-ps (as well as the module p-modu-4-ps in (Zhang et al , 2012a)), where the positive correlations between the modular miRNAs and mRNAs could not be simply explained by a regulator-target mechanism.…”
Section: Discussionmentioning
confidence: 99%